Properties of Fibrinogenolysis and Fibrinolysis Products in Immune Assays - Beller, F. K; Maki, M (Thrombosis and Haemostasis, 1967)
An evaluation of split products derived from fibrinogen and fibrin gave the following results:1. Fibrinogen can be assayed in the presence of split products by the following techniques: Fibrinogen assay according to Ratnoff and Menzie and immuno radial diffusion after heat precipitation. Using the thrombin clotting time the recovery is improved if the incubation time is extended up to 24 hrs and further by adding Ca ions.2. On immune electrophoresis split products separate only in serum but not in plasma. If however, euglobulin fractions and acidified plasma were prepared separation occured.3. The larger split product, fraction D, derived from fibrinogen is heat labile, whereas it is heat stabile if it is derived from fibrin. Thrombin as well as large concentrations of plasmin stabilize the split product from fibrinogen against heat.4. The prolongation of thrombin clotting time in the presence of fibrinogenolysis split products disappears after heating. Split products derived from fibrin do not prolong the thrombin clotting time. A prolongation however, develops after heating.5. It is suggested that differentiation between intravascular coagulation and proteolysis is possible on the basis of the combined techniques of immune electrophoresis, radial diffusion method and the thrombin clotting time before and after heating.